2021
DOI: 10.1097/mao.0000000000003295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cranioplasty Techniques Following Translabyrinthine Surgery: Implications for Postoperative Pain and Opioid Usage

Abstract: Objective: To assess differences in postoperative pain, opioid usage, and surgical outcomes between cranioplasty using abdominal fat graft (AFG) versus hydroxyapatite cement (HAC) following translabyrinthine surgery. Study Design: Retrospective case control. Setting: Tertiary referral center. Patients: Sixty translabyrinthine procedures were evaluated, including 30 consecutive HAC patients and 30 matched AFG patients. Patients were matched by age, gender, body mass index, and tumor size. Intervention: Craniopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…19 Twenty-one out of 25 studies reported that the The ET could be occluded (or packed), or not treated at all. [15][16][17][18][19][20]23,[25][26][27][28]31,32,34,35,36,38,41,49,[55][56][57][58] Two studies analysed the impact of ET closure on CSF rates, both concluding ET packing did not influence CSF leak rates. 19,23 Considering the materials used to pack the eustachian tube, the many studies reported the use of muscle, typically harvested from the temporalis or from the sternocleidomastoid.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…19 Twenty-one out of 25 studies reported that the The ET could be occluded (or packed), or not treated at all. [15][16][17][18][19][20]23,[25][26][27][28]31,32,34,35,36,38,41,49,[55][56][57][58] Two studies analysed the impact of ET closure on CSF rates, both concluding ET packing did not influence CSF leak rates. 19,23 Considering the materials used to pack the eustachian tube, the many studies reported the use of muscle, typically harvested from the temporalis or from the sternocleidomastoid.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…19,23 Considering the materials used to pack the eustachian tube, the many studies reported the use of muscle, typically harvested from the temporalis or from the sternocleidomastoid. [15][16][17][18][19][20]23,[25][26][27]31,32,36,38,56,58 Muscle was combined with either fascia 19,20,23,26,58 , oxidised cellulose (Surgicel) 17,19,[25][26][27]36,38 or tissue glue. 16,17,56 Other alternatives to muscle grafts for ET packing were: polytetrafluoroethylene and carbon filaments (Proplast) 19 , high molecular weight polyethylene (Plastipore) 19 , surgicel 19,41 , dry periosteum 17,32,34,55,57 , or the incus.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations